(3efgGL GdfLGIs - (3GdcGTj Ch GdcGTGfj, , GdajV, eMeO Hf eQJVi Hf eMehO, J (B1091(3g`s ((3MSjf Hf Ydj GdMdjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG ddOjf Gdbhje hGdfgL GdeSJbje(B... (3CeG HYO ajbhd(B... (3gPG cJGH(B... (3HjfJ ajg GdYde GdPj jJhba Ydjg GdfLGI aj GdBNQI(B...s
(3BNQgG (B:s
(3aeG CaSOg gPG GdeZQhQ HCYeGdg CcKQ eeG CUdMg HCbhGdg (B... (3Ke EjGc Cf Jchf ef GdaQjb GdKGdK aJgdc gdGcG dG jQLi adGMc hdG jfJXQ UdGMcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B617s
(3GdCYdGe(B: (3L(B5(3, U(B290s
(3EjVGM Gdecfhf(B: (3L, U(B589s
(3GdCYdGe(B: (3L(B5(3, U(B290s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs